Clonagem de canistel por estaquia - Chiamolera, Fernando Marcelo [UNESP]; Silva, Adriana De Castro Correia Da; Sabião, Rafael Roveri [UNESP]; Cunha, Tatiana Pagan Loeiro Da [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The yellow sapote is native to southern Mexico and Central America, and its fruits have high content of carotenoids and vitamin A. Its propagation is done through seed, resulting in considerable genetic variability among individuals, being preferable vegetative propagation, in order to fix desirable characteristics. Thus, the aim of this study was to evaluate the vegetative propagation by cuttings of semiherbaceous branches of yellow sapote, according to four genotypes and four concentrations of IBA. Cuttings were semi-herbaceous apical, maintained with a pair of leaves, under intermittent mist for 120 days. A completely randomized experimental design was use, in a 4×4 factorial (yellow sapote genotypes × IBA concentrations) with four replicates and ten cuttings per plot. It was evaluate the percentage of survival, leaf retention, rooting, callus, average number and length of roots per cutting. The PC-1 genotype was superior to others in all variables, with emphasis on the rooting of cuttings exceeding 60%. The IBA concentrations (0; 1,000; 3,000 and 5,000 mg L-1) did not influence survival, leaf retention and rooting but increased the number and length of roots compared to control treatment (without IBA). There were differences in rooting capacity to among genotypes of yellow sapote, being the best response obtained with PC-1. The IBA concentration 3,000 mg L-1 results in greater number and length of roots in the yellow sapote cuttings.

O canistel é nativo do sul do México e América Central e seus frutos apresentam elevado teor de carotenoides e vitamina A. Sua propagação é feita via sementes, resultando em considerável variabilidade genética entre os indivíduos, sendo a propagação vegetativa preferível, a fim de fixar características desejáveis. Assim, o objetivo deste trabalho foi avaliar a propagação vegetativa por estaquia de ramos semi-herbáceos de canistel, em função de quatro genótipos e quatro concentrações de AIB. Foram utilizadas estacas semiherbáceas apicais, mantidas com um par de folhas, sob nebulização intermitente, por 120 dias. O delineamento experimental foi o inteiramente casualizado, em esquema fatorial 4×4 (genótipos de canistel × concentrações de AIB), com quatro repetições e dez estacas por parcela. Foram avaliados a porcentagem de sobrevivência, a retenção foliar, o enraizamento, o calejamento, o número e o comprimento médio de raízes por estaca. O genótipo PC-1 foi superior aos demais, em todas as variáveis avaliadas, com destaque para o enraizamento das estacas, superior a 60%. As concentrações de AIB (0; 1.000; 3.000 e 5.000 mg L-1) não influenciaram na sobrevivência, retenção foliar e enraizamento das estacas, mas aumentaram o número e o comprimento de raízes em relação ao tratamento-controle (sem AIB). Há diferença na capacidade de enraizamento das estacas entre os genótipos de canistel, sendo a melhor resposta obtida com PC-1. A concentração de 3.000 mg L-1 de AIB resulta em maior número e comprimento de raízes nas estacas de canistel.
Cloning of yellow sapote by cutting
Keywords: Pouteria campechiana; AIB; enraizamento; produção de mudas; Pouteria campechiana; IBA; rooting; seedling production